2012
DOI: 10.1111/j.1466-7657.2012.01012.x
|View full text |Cite
|
Sign up to set email alerts
|

A critical analysis of undergraduate students' cultural immersion experiences

Abstract: HARROWING J.N., GREGORY D.M., O'SULLIVAN P.S., LEE B. & DOOLITTLE L. (2012) A critical analysis of undergraduate students' cultural immersion experiences. International Nursing Review Purpose:  This paper is concerned with the impact of an international health promotion experience on the understanding of culture among university students. Such immersion experiences are often cited as a strategy to prepare nurses for culturally appropriate practice. We describe students' epistemic movements over time with respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 22 publications
(30 reference statements)
0
25
0
Order By: Relevance
“…These findings impact nursing curriculum planning in including cultural immersion experiences in the curriculum, and are congruent with other findings in the literature. [11,[41][42][43][44][45][46][56][57][58][59][60][61][62][63][64] Given the importance of cultural immersion in promoting cultural competence among nursing students denoted in the literature, nursing faculty need to consider incorporating cultural immersion in the curriculum through strategic curriculum planning while remaining cognizant of available resources. Study abroad experiences are preferable, but require time, resources, and adequately prepared faculty facilitators.…”
Section: Teaching Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings impact nursing curriculum planning in including cultural immersion experiences in the curriculum, and are congruent with other findings in the literature. [11,[41][42][43][44][45][46][56][57][58][59][60][61][62][63][64] Given the importance of cultural immersion in promoting cultural competence among nursing students denoted in the literature, nursing faculty need to consider incorporating cultural immersion in the curriculum through strategic curriculum planning while remaining cognizant of available resources. Study abroad experiences are preferable, but require time, resources, and adequately prepared faculty facilitators.…”
Section: Teaching Methodsmentioning
confidence: 99%
“…Some studies that used this model showed its effectiveness in guiding teaching and learning methods, but there is a need for further research identifying predictors of cultural competence. [23][24][25][26][27][28][29][30][31][32][33][34][35][36] Many approaches were noted in the literature related to cultural competence in the curriculum, and are summarized as follows: the need to critically evaluate implementation and evaluation methods of cultural concepts in the curriculum, [4,9,10,12,15,17,38,39] use of a stand-alone course on culture in the curriculum, [22,30] integration of cultural concepts throughout the curriculum, [12,13,40] use of service learning projects and cultural immersion projects to increase cultural competence, [11,12,[41][42][43][44][45][46][47] lack of qualified faculty members to teach cultural concepts, [23,48] need for course material to adapt to the changing learning needs of students, [45] and international collaboration among teaching institutions to teach cultural competence. [6,35,39,49] While the above note...…”
Section: Introductionmentioning
confidence: 99%
“…Immersion experiences and study abroad experiences provide opportunities for students to learn about other cultures within the context of the culture resulting in improved cultural self-awareness and sensitivity (Charles et al, 2014;Harrowing, Gregory, O'Sullivan, Lee, & Doolittle, 2012).…”
Section: Online Journal Of Cultural Competence In Nursing and Healthcarementioning
confidence: 99%
“…Nevertheless, there is an agreement that international placements can provide an important awakening, which can lead to further awareness about sociocultural differences. Several authors underscore that education about ethnicity, racism, sociopolitical perspectives and social determinants of health are crucial for students to make sense of their experiences (Alpers & Hanssen, ; Culley, ; Harrowing, Gregory, O'Sullivan, Lee, & Doolittle, ; Mkandawire‐Valhmu & Doering, ; Racine & Perron, ). Following up on the critique presented above, we argue that an awareness of the political and social context can be fostered and enhanced through various supportive educational interventions during the entire graduate educational process.…”
Section: Introductionmentioning
confidence: 99%